The entrepreneur–environment nexus: Uncertainty, innovation, and allocation - York, Jeffrey G.; Venkataraman, S. (Journal of Business Venturing, 2010)
We build upon a recent stream of research that has proposed entrepreneurship as a solution to, rather than a cause of, environmental degradation. Our proposition is that under certain conditions entrepreneurs are likely to supplement, or surpass, the efforts of governments, NGOs and existing firms to achieve environmental sustainability. Entrepreneurs can contribute to solving environmental problems through helping extant institutions in achieving their goals and by creating new, more environmentally sustainable products, services and institutions. Our model illustrates how entrepreneurs 1) address environmental uncertainty, 2) provide innovation and 3) engage in resource allocation to address environmental degradation.